A NOVEL TECHNIQUE FOR MULTIPLE FAULTS AND THEIR LOCATIONS DETECTION AND START ELECTRODE SELECTION IN MICROFLUIDIC DIGITAL BIOCHIP - MUKTA MAJUMDER (Journal of Innovative Optical Health Sciences, 2013)
A device, that is used for biomedical operation or safety-critical applications like point-of-care health assessment, massive parallel DNA analysis, automated drug discovery, air-quality monitoring and food-safety testing, must have the attributes like reliability, dependability and correctness. As the biochips are used for these purposes; therefore, these devices must be fault free all the time. Naturally before using these chips, they must be well tested. We are proposing a novel technique that can detect multiple faults, locate the fault positions within the biochip, as well as calculate the traversal time if the biochip is fault free. The proposed technique also highlights a new idea how to select the appropriate base node or pseudo source (start electrode). The main idea of the proposed technique is to form multiple loops with the neighboring electrode arrays and then test each loop by traversing test droplet to check whether there is any fault. If a fault is detected then the proposed technique also locates it by backtracking the test droplet. In case, no fault is detected, the biochip is fault free then the proposed technique also calculates the time to traverse the chip. The result suggests that the proposed technique is efficient and shows significant improvement to calculate fault-free biochip traversal time over existing method.